Conformal symmetry and composite operators in the O(N)3 tensor field theory - Benedetti, Dario; Gurǎu, Rǎzvan; Suzuki, Kenta (Journal of high energy physics, 2020)
We continue the study of the bosonic O(N )3 model with quartic interactions and long-range propagator. The symmetry group allows for three distinct invariant 𝜙4 composite operators, known as tetrahedron, pillow and double-trace. As shown in [1, 2], the tetrahedron operator is exactly marginal in the large-N limit and for a purely imaginary tetrahedron coupling a line of real infrared fixed points (parametrized by the absolute value of the tetrahedron coupling) is found for the other two couplings. These fixed points have real critical exponents and a real spectrum of bilinear operators, satisfying unitarity constraints. This raises the question whether at large-N the model is unitary, despite the tetrahedron coupling being imaginary.
Im Titel ist die Zahl "3" hochgestellt
Gesehen am 07.10.2022